PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SMART APPS CREATOR PADA TEMA 9 SUBTEMA 3 MANUSIA DAN BENDA DI LINGKUNGANNYA PEMBELAJARAN 5 - Niken Nuryandis; Dadang Kurnia; Dita Destiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Learning Media Based on Smart Apps Creator on Theme 9 Sub-theme 3 Humans and Objects in Their Environment Learning 5. This research is Research and Development (RnD), with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This study aims to (1) develop learning media based on smart apps creator (2) determine the feasibility of learning media based on smart apps creator. The research was conducted at SDN Bangka 3, Bogor City, with a total of 26 students for the 2022-2023 academic year. The research begins by analyzing students, teaching materials, curriculum, then making product designs. Then develop the product and validate the product with experts in the field, which is then carried out with limited trials with respondents. The results of the validator trials and student response questionnaires showed an average percentage of 91.72%. The level of effectiveness of smart apps creator-based learning media on student learning outcomes gets the highest score of 100 and the lowest 80 with an average of 88.76%. This shows that the smart apps creator-based learning media developed is effective and feasible to use.